1998
DOI: 10.1103/physrevc.57.2453
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical study of fission process and estimation of prescission neutron multiplicity

Abstract: The dynamics of fission has been studied by solving Euler-Lagrange equations with dissipation generated through one and two body nuclear friction. The average kinetic energies of the fission fragments, prescission neutron multiplicities and the mean energies of the prescission neutrons have been calculated and compared with experimental values and they agree quite well. A single value of friction coefficient has been used to reproduce the experimental data for both symmetric and asymmetric splitting of the fis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…In the fission process, in accordance with our previous work [10], the shape of the fissioning nucleus is described in terms of the elongation axis (the neck parameter of [11] taken equal to zero). Thus, in the dynamical description we have the elongation axis, its relative orientation with respect to an inertial system and respective velocities associated with them as the stochastic variables interacting with a large number of internal nucleonic degrees of freedom constituting a heat bath at temperature T determined by the excitation energy available to it.…”
Section: A the Formalismmentioning
confidence: 82%
See 4 more Smart Citations
“…In the fission process, in accordance with our previous work [10], the shape of the fissioning nucleus is described in terms of the elongation axis (the neck parameter of [11] taken equal to zero). Thus, in the dynamical description we have the elongation axis, its relative orientation with respect to an inertial system and respective velocities associated with them as the stochastic variables interacting with a large number of internal nucleonic degrees of freedom constituting a heat bath at temperature T determined by the excitation energy available to it.…”
Section: A the Formalismmentioning
confidence: 82%
“…It has already been shown that the tangential friction which causes dissipation of relative angular momentum L into the angular momenta I 1 , I 2 of the two fragments does not have any significant effect on the physical observables [10] . Besides, no experimental observation of angular momentum dispersion of fission fragments are available in the litterature.…”
Section: A the Formalismmentioning
confidence: 99%
See 3 more Smart Citations